2010
DOI: 10.1038/emboj.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic pH is a second messenger for glucose and regulates the PKA pathway through V-ATPase

Abstract: Glucose is the preferred carbon source for most cell types and a major determinant of cell growth. In yeast and certain mammalian cells, glucose activates the cAMPdependent protein kinase A (PKA), but the mechanisms of PKA activation remain unknown. Here, we identify cytosolic pH as a second messenger for glucose that mediates activation of the PKA pathway in yeast. We find that cytosolic pH is rapidly and reversibly regulated by glucose metabolism and identify the vacuolar ATPase (V-ATPase), a proton pump req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
321
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(341 citation statements)
references
References 82 publications
19
321
1
Order By: Relevance
“…The mechanism of V-ATPase regulation by reversible dissociation was first described in yeast (9) and insects (11) but has since been found to be a general mechanism for enzyme regulation in higher eukaryotes (32)(33)(34). Although this unique mode of regulation is well documented, the molecular mechanism remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of V-ATPase regulation by reversible dissociation was first described in yeast (9) and insects (11) but has since been found to be a general mechanism for enzyme regulation in higher eukaryotes (32)(33)(34). Although this unique mode of regulation is well documented, the molecular mechanism remains poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a number of environmental signals have been linked to enzyme dissociation, mainly related to metabolism and specifically glycolysis (10). Changes in enzyme association have been linked to phosphorylation (47), extracellular conditions (48), pH changes (34,48), and subcellular localization (33,49). Further complicating the understanding of this mechanism are the number of cellular binding partners for subunits likely to be involved in enzyme regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Control of one by the other, as suggested by our results, may reflect unanticipated inter-ATPase communication. Indeed, V-ATPase function has been linked to Wnt (40) and Notch (41) signaling and to nutrient-responsive signaling through pH control (42). Nutrient-responsive signaling has also been linked to mitochondrial DNA damage (43).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it may be that the vph1⌬ mutation also compromises glucose signaling to Pma1. Significantly, recent work has suggested that the V-ATPase may play a role in mediating certain glucose signals (29); it is possible that the pathways that activate Pma1 in response to glucose are affected by the vph1⌬ mutation. Cytosolic acidification without Pma1 mislocalization was also observed after a brief treatment with the V-ATPase inhibitor concanamycin A (12), also suggesting a second mechanism for down-regulation of Pma1 activity.…”
Section: Discussionmentioning
confidence: 99%